1994
DOI: 10.1289/ehp.94102s3181
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane signals and protooncogene induction evoked by carcinogenic metals and prevented by zinc.

Abstract: Cd2+ provokes an immediate production of inositol trisphosphate and the release of Ca2+ from internal stores in human fibroblasts and some other mammalian cells. Ni2+, Co2+, Fe2+, and Mn2+ evoke the release of stored Ca2+, but are less potent than Cd2+ (apparent Ko05 = 40 nM). Zn2+ and Cu2+ competitively inhibit Ca2+ release evoked by Cd2, without affecting Ca2+ release by hormones such as bradykinin. Zn2+ has the same apparent Ki value (80-90 nM) towards the five agonist metals, which suggests that the metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated that metals with chemical characteristics similar to Cd 2+ protect against the biochemical and toxic effects of Cd 2+ in a competitive manner [4,38]. The results obtained with Fura-2-loaded cells resembled those observed in I sc -and Cl --transport experiments [14], since pre-treatment with Zn 2+ or Ni 2+ at 400 M completely removed [DCa 2+ ] Cd .…”
Section: Interaction Studiesmentioning
confidence: 69%
“…Several studies have demonstrated that metals with chemical characteristics similar to Cd 2+ protect against the biochemical and toxic effects of Cd 2+ in a competitive manner [4,38]. The results obtained with Fura-2-loaded cells resembled those observed in I sc -and Cl --transport experiments [14], since pre-treatment with Zn 2+ or Ni 2+ at 400 M completely removed [DCa 2+ ] Cd .…”
Section: Interaction Studiesmentioning
confidence: 69%
“…Previous studies showed that nickel-induced signal transduction pathways involved c-Myc, Ras, c-Jun, and NFκB [6,[8][9][10]. They can be activated via Ras/MEK/ERK pathway [15] or P13K/Akt pathway [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is likely to involve in genetic and epigenetic routes. Previous studies reported that nickel can produce oxidative DNA damage, inhibit DNA repair activity [5], effect signal transduction pathways, such as blocking Ca 2+ channels, and release stores of free intracellular Ca 2+ in a variety of systems, inactivate c-Myc, Ras, c-Jun, and NFκB [6][7][8][9][10]. Epigenetic effects of nickel includes the induction of DNA methylation and histone deacetylation, as well as activation or silencing of certain genes, especially those involved in cellular response to hypoxia [5,11].…”
mentioning
confidence: 99%